L'Homme et le milieu végétal Analyses anthracologiques de six gisements des Préalpes au Tardi- et au Postglaciaire - Thiebault, Stéphanie (Documents d'archéologie française, 1988)
Stéphanie Thiébault is a Research Fellow with the CNRS. In this work, based upon her doctoral thesis, the author considers the relationship between Man and the plant world during the Holocene period and examines this era of significant cultural change along a south-north axis from the Mediterranean to the Savoy. This comprehensive study is the first of its kind to be carried out in the area for this period: over 10,000 charcoal samples, taken from six highly-stratified deposits in the south-western Pre-Alps are analysed and the wood species identified. As a result, this book is also an excellent introduction to the methods of anthracology (the identifying of wood species from charcoal remains). The author assesses the method's potential for ecological reconstructions of ancient landscapes and climates, as well as its implications for palaeethnology. Conceived as the first stage of a larger project, this study lays the ground-work for future discussion of palaeobotany in the regions examined.